Analysis of Koi Fish Marketing Strategy at CV Agro Koi, Kediri Regency - Rafikhein Novia Ayuanti; Imam Mukhlis (Formosa Journal of Science and Technology, 2023)
The aim of this research is to find out how to implement koi fish marketing strategies at CV. Agra Koi uses SWOT analysis. Using SWOT analysis as a strategy formulation tool, through SWOT Analysis you can find out internal and external business factors, this series is an application of marketing promotion at CV. Agra Koi Farm Kediri. In this research, researchers used descriptive research aimed at understanding the meaning and uniqueness of the object being studied. And using a qualitative approach. The research location is in Rembang village, Ngadiluwih, Kab. Kediri. Data collection techniques in this research used in-depth interviews, observation, and documentation.